2014
DOI: 10.1177/039463201402700418
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Bacteria Lactobacillus and Bifidobacterium Attenuate Inflammation in Dextran Sulfate Sodium-Induced Experimental Colitis in Mice

Abstract: It is widely accepted that inflammatory Bowel disease (IBD) arises from a dysregulated mucosal immune response to the enteric microbiota in the gut of a genetically susceptible individual. No definitive therapies are available for this inflammatory disorder. Therefore it became imperative to develop new strategies for treating this disease. Probiotics have emerged as a potential new therapeutic strategy for IBD, however their exact mechanisms of action is still poorly defined. In this study, we address the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 27 publications
4
62
0
2
Order By: Relevance
“…There is growing body of evidence that suggest that probiotics and heminths may have potential use as antiinflammatory agents in IBD by inducing antiinflammatory cytokines pattern. The results of our studies and others demonstrated that some probiotics such as Bifidobacterium infantis and Bifidobacterium longum downregulate proinflammatory cytokines IFN-γ, IL-12, TNF-α, and IL-8 production and stimulate immunoregulatory cytokine IL-10 production [33,[90][91][92]. Moreover, it has been reported that B. infantis feeding in DSS-induced colitis model downregulate IL-17A expression and induce IL-10 production restoring thereby the TH17/ Tregs balance [93,94].…”
Section: Therapeutic Implicationssupporting
confidence: 51%
“…There is growing body of evidence that suggest that probiotics and heminths may have potential use as antiinflammatory agents in IBD by inducing antiinflammatory cytokines pattern. The results of our studies and others demonstrated that some probiotics such as Bifidobacterium infantis and Bifidobacterium longum downregulate proinflammatory cytokines IFN-γ, IL-12, TNF-α, and IL-8 production and stimulate immunoregulatory cytokine IL-10 production [33,[90][91][92]. Moreover, it has been reported that B. infantis feeding in DSS-induced colitis model downregulate IL-17A expression and induce IL-10 production restoring thereby the TH17/ Tregs balance [93,94].…”
Section: Therapeutic Implicationssupporting
confidence: 51%
“…In both patients and animal models of IBD, a positive correlation between the overproduction of pro-inflammatory cytokines (e.g., IL-1b, TNF-α, IFN-γ) and an overexpression of iNOS was found. This expression was primarily detected in the lamina propria mononuclear cells and the colon epithelial cells of the inflamed mucosa [6,16,17,27,30,71,72] . Several studies conducted on a dextran sulfate sodium (DSS)-induced experimental model of colitis in BALB/c mice indicated that the neutralization of endogenous TNF-α and/or IFN-γ ameliorated the chronic colitis and concomitantly decreased the generation of NO.…”
Section: Cytokine Regulation Of No In Ibdmentioning
confidence: 99%
“…The strain was cultured in MRS broth (Merck, Germany) pre pared as night cultures at 37ºC aerobically and provided in a dose of 3x10 9 CFU of strain/1 mL. Then 0.5 mL of lactobacilli strains mixed with 9 mL of pasteurized milk (20-22ºC) was fi lled into bottles and administered every day.…”
Section: Probiotic Strainmentioning
confidence: 99%
“…Then 0.5 mL of lactobacilli strains mixed with 9 mL of pasteurized milk (20-22ºC) was fi lled into bottles and administered every day. Each rat received approximately 1.5x10 9 CFU lactobacilli via the oral route.…”
Section: Probiotic Strainmentioning
confidence: 99%
See 1 more Smart Citation